Effect of free and immobilised stem bromelain on protein haze in white wine. (18th September 2014) - Benucci, I.; Esti, M.; Liburdi, K.
Abstract Background and Aims Several studies have investigated the effectiveness of several proteolytic enzymes in free form as a treatment alternative to bentonite fining for wine stabilisation. This work tested the feasibility of stem bromelain, free or immobilised on a chitosan support, to reduce white wine protein haze potential. Methods and Results The kinetic behaviour of stem bromelain, in free form and covalently immobilised on chitosan beads, was studied in 12 unfined white table wines fortified with a tripeptide chromogenic substrate. The effectiveness of the protease on wine hazing potential was determined by treating the wines in a laboratory‐scale stirred reactor, and the heat test was applied to evaluate the decrease in nephelometric turbidity units. Immobilised protease was active towards the synthetic substrate and in reducing hazing potential of the wine. The effect of wine components on bromelain proteolytic behaviour, as investigated by principal component analysis, was much more noticeable for the free enzyme (in decreasing order of importance: pH, total phenolic substances, free and total sulfur dioxide) than for the immobilised form. Conclusions An amount of 10 g/L biocatalyst (bromelain immobilised on chitosan beads), after a 24‐h treatment in a laboratory‐scale stirred reactor, revealed a high capacity to reduce wine haze potential (approximately 70%), which was unaffected by wine composition. Significance of the Study Immobilised bromelain appears a suitable treatment alternative to bentonite fining for white wine haze stabilisation.